Social development : challenges faced in an unequal and plural society - Gore, M. S. (Jaipur : Rawat Publications, 2003)
With reference to India; articles.
Includes bibliographical references and index.
Keywords: Social planning -- India; Cultural pluralism -- India; Equality -- India